Awareness of risk factors of cardiovascular disease among patients with diabetes mellitus attending diabetic clinic of BP Koirala Institute of Health sciences - Khanal, Dina; Parajuli, Pushpa; Mehta, Ram Sharan; Mandal, Gayanand (Journal of Chitwan Medical College, 2021)
Background: Cardiovascular disease (CVD) is the leading cause of death worldwide. Awareness of risk factors of CVD is the first step towards effective preventive strategies to combat the CVD burden in diabetes patients. This study aimed to assess the awareness of risk factors of CVD among patients with diabetes mellitus attending diabetic clinic of B.P Koirala Institute of Health Sciences (BPKIHS). Methods: A cross- sectional study was conducted among 112 patients with diabetes in diabetic clinic of BPKIHS. Convenient sampling was used for data collection over duration of six weeks using interview schedule by HDFQ II tool. The data were analyzed in the statistical package for social science software (SPSS) 16 versions and analyzed using descriptive and inferential statistics. Results: Majority of respondent were aware about common risk factors such as (83.9%) smoking, (78.6%) physical activity, (75%) increasing age, (75.9%) high blood pressure, (71.4%) overweight respectively. Whereas most of the respondents were not aware about high cholesterol, fatty diet, preventive strategies and association of diabetes with CVD. Awareness was statistically significant with educational status, monthly income, residence, CVD information received and co-morbid condition as a heart disease. Conclusions: Based on finding most of the respondents were aware about common risk factor even though they have inadequate level of awareness on overall risk factors of CVD among the risk factor they were poorly aware about cholesterol, gender and preventive aspect. So Effective education on diet and appropriate preventive strategies of CVD are indeed important to reduce CVD burden in diabetes patients.